Religion and Socioeconomic Attainment in Ghana - Heaton, T.; James, S.; Oheneba-Sakyi, Y. (Religious Research Association, Inc, USA, 2009)
Substantial research has documented the association between religion and socio-economic attainment in Western nations. As Christianity has expanded and been transformed in developing nations and the confrontation between Islam and the West has received growing attention, the role religion plays in socioeconomic inequality continues to be a critical issue. We use the Ghana Demographic and Health Survey for 2003 to test the relationship between religious affiliation and socioeconomic attainment. Religious differences in socioeconomic outcomes are substantial in Ghana. Mainline Protestants have a significant advantage in education and wealth. Catholics and other Christians have intermediate values on these socioeconomic outcomes. Muslims and those without attachments to formal religious groups have a significant disadvantage. Educational differences are particularly important because they account for some of the differences in wealth. Moreover, differences in the rates of school enrolment signal that inequality will persist in the next generation.
Keywords: Socioeconomic attainment; religious affiliation; inequalities; school enrolment; educational differences; wealth creation; Ghana